The Modern Methods of Data Analysis in Social Research - Ikram Harouni (Social Empowerment Journal, 2024)
This study aims to highlight the significance and various dimensions of utilizing the Python language in the field of social sciences. Python is widely recognized as one of the most frequently employed programming languages, primarily due to its user-friendly nature and suitability for data analysis in social research. In this study, particular emphasis is placed on the Pandas library, which holds a prominent position in data analysis for social research. The library offers robust tools for data analysis, manipulation, and the execution of mathematical and statistical operations in an efficient and accessible manner. The study has concluded that learning programming languages and using them in data analysis in social sciences has become crucial nowadays to understand, analyze and interpret the contemporary society, as well as to generate new scientific perspectives and produce knowledge that corresponds to the rapid changes in the social field.